Knowledge about hepatitis B and influencing factors among the residents in Qingdao: a cross-sectional study - Wenliang Fei; Tingting Xiao; Xiaofan Li; Feng Yang (Journal of Infection in Developing Countries)
Introduction: This study investigated the status of knowledge on hepatitis B among the residents in Qingdao and provided a reference for improving relevant public awareness strategies.